Synthesis, characterization, and reactivity studies of η 5 -cyclopentadienyliron dicarbonyl 4- (dimethylamino)phenyldiphenylphosphine iodide and di(µ2-chloro)(η 5 -cyclopentadienyl)4- (dimethylamino)phenyldiphenylphosphine iron-palladium iodide - Tong, Yong Yao (2023)
A study on synthesis of new organometallic complexes, [CpFe(CO)2(PPh2(p-C6H4NMe2))]I (2) from the reactions of CpFe(CO)2I (1) with 4- (dimethylamino) phenyldiphenylphosphine via microwave-assisted reaction in toluene at 110 °C for 30 minutes. Besides, another new bimetallic complexes, [CpFe(PPh2(p-C6H4NMe2)(µ-Cl)2Pd)]I4 (3) was synthesized from the microwave-assisted reaction of complex 2 with palladium chloride in acetonitrile at 60 °C for 3 hours. The progress of the reaction was monitored by Thin Layer Chromatography (TLC) and the compounds were isolated via silica gel column chromatography then further purified by recrystallization at -20 °C. These new complexes were characterized by Fourier Transform Infrared Spectroscopy (FTIR), 1H, 13C and 31P Nuclear Magnetic Resonance (NMR) Spectroscopy, UV-Visible Spectrophotometry, III Elemental Analysis, Electrospray-Ionization Mass Spectrometry (ESI-MS). The molecular structures of the complexes along with their synthetic pathways were proposed based on various spectroscopy results and the NMR tube reactions, C,H,N elemental analysis and fragmentation patterns of complexes 2 and 3 from the ESI MS. Furthermore, antioxidant properties of the complex 2 was studied using 2,2- diphenyl-1-picrylhydrazyl (DPPH) assay